Kajian Pemupukan NPK dan Jarak Tanam pada Produksi Antosianin Daun Kolesom - Mualim, Leo; Aziz, Sandra Arifin; Melati, Maya (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2009)
The effects of NPK fertilization and plant spacing on leaf anthocyanin production of Talinum triangulare (Jacq.) Willd. were studied. A factorial experiment was used to study the combination of two factors i.e. NPK fertilization (no fertilization, NPK, NP, NK, and PK) and plant spacing (100 cm x 45 cm, 100 cm x 60 cm, 100 cm x 75 cm). These combinations were arranged in randomized block design, with three replications. The result showed that there was no effect of plant spacing and interaction between two factors. Application of NP (minus K) fertilizer gave the lowest value for almost all parameter except shoot/root ratio. This result suggested that fertilization played significant role in increasing anthocyanin production and the limiting factor was potassium. Key words: Talinum triangulare, NPK fertilization, anthocyanin production